The lost world of the British Labour Party? Community, infiltration and disunity. Issue 4 (3rd December 2018) - Watts, Jake
Abstract Drawing on Benedict Anderson's notion of the 'imagined community', this article examines the evolution of the British Labour Party's sense of self as an organisation. Accordingly, the analysis interrogates the interrelated elements of history, culture, identity and party structure. It is argued that Labour has moved substantially from the collective class-based notions it once used to define its politics and effectively demarcate its boundaries. In place of these, an increasing focus has been placed on giving the party's political practices an outward-looking, diverse and more individualistic focus. Consequently, Labour's difficulties during the leadership election of 2015 and since are rooted in the combination of this prolonged push to build a new movement beyond its traditional borders and the persistence of historically grounded tribal concerns about the vulnerability of the party to infiltration.